PERCEPTIONS ON ONLINE LANGUAGE TEACHING PEDAGOGY - Magdalena Kartikasari Tandy Rerung (Journal of English Language Teaching and English Linguistics, 2021)
The following research is intended to find out how lecturers deal with English teaching during the full-online learning program. However based on the online teaching pedagogy, teachers who are expert in the field are those who can make use of ICT tools and equipment to make the learning progress is accessible and also interactive. Based on Compton (2009). Additionally, he also mentions does not mean that a good teacher in face-to-face interaction can also be a good one in virtual classroom. To meet the criteria, the research will ask the questions on what are the perceptions and activites used by the English lecturers once they adopted the online teaching method. Participants were gathered from 15 lecturers who are currently teaching Business English for the first semester students. The LMS used is provided by Bunda Mulia University where the lecturers and students interacting through forum discussion. Hopefully the result could evaluate how far the teachers make use the online teaching platform and whether they also used other sources to support their online classroom.Â